Efeito da cor do cimento resinoso e do tipo de aparelho fotoativador na estabilidade de cor de laminados cerâmicos de fina espessura - Zinelli, Rafaella Ronchi (2019)
The aim of this study was to evaluate the color stability of thin ceramic laminates after cementation with different-color photoactivated resin cements using conventional (monowave) or broad-spectrum (polywave) light curing unit; as well as the degree of conversion of the different photoactivated cements with both light curing units. Three photoactivated resin cements were used: AllCem Veneer APS (AC), RelyX Veneer (RX) and Variolink Esthetic (VE) in 3 colors each (high opacity clear (OW, WO e Light+), medium opacity clear (E-bleach, B0,5 e Light) and medium opacity dark (A3, A3 e Warm+) for cementation of ceramic laminates (VITABLOCS, Mark II, color 1M1) 0.8 mm thick on bovine enamel. The specimens were randomly distributed in 18 groups according to the cementing agent, cement color and light curing unit used (n=10). Photoactivation was performed using a monowave Radii Plus (SDI) or a polywave Valo (Ultradent) ligth curing unit. After cementation, the specimens were stored in distilled water at 37ºC. The CIELab system color parameters were evaluated for the calculation of ΔE00 with a spectrophotometer (Easyshade Advance) at 24 hours (baseline) and after 180 days of cementation. Fourier transformation infrared spectroscopy was used to determine the level of light curing of the cement through the ceramic material with each light source after 24 hours. The degree of conversion was calculated as a percentage of experimentally versus maximally polymerized resin cement. Data on color change and degree of conversion were subjected to statistical analysis (2-way ANOVA, light curing unit and cement/color, and Tukey tests) with a significance level of 5%. It can be observed that most groups presented color stability over time. There was no significant difference for the type of light curing unit or for the interaction device* cement/color (p> 0.05). There was a difference in color stability only for the individual cement/color factor (p <0.05). VE cement, in Warm+ and Light colors, presented higher values of ΔE00 compared to AC cement, in OW and E-bleach colors, regardless of the light curing unit used. Regarding the degree of conversion, RX cement, regardless of color, presented the highest GC values for both units (p <0.05). There was a significant difference with higher conversion degree values for the polywave unit compared to monowave one in most cements. It was concluded that the type of light curing unit did not affect color stability, but significantly interfered with the degree of conversion of the different types of cement. The different types of cements/colors influenced the color stability of the ceramic/cement set, regardless of the light curing unit used.